Reintrodução de aves oriundas do comércio ilegal no Brasil: estudo de caso com Sporophila albogularis, Sporophila nigricollis E Sicalis flaveola em uma área de caatinga. - Cavalcanti, Tarsila Almeida (2011)
Yearly, thousands of wild animals are removed from the wild in Brazil, even though environmental legislations prohibit such practice. Some of the specimens are firstly seized by the committees in charge of traffic control and are then sent to CETAS, a fact which creates overcrowded situations due to the limited physical space and destination difficulties. This study discusses the issue of reintroducing animals in the wild as the main destination measurement of specimens by CETAS in Brazil. Until recently, most kinds of reintroductions were carried out without any type of monitoring or research aim. Due to a large number of unsuccessful attempts, there has been, in the last years, an increase in the number of monitored reintroductions, with the inclusion of tests and hypothesis experimentation. In Brazil, the reintroduction of animals to their natural habitats has been frequently carried out by control committees. Nevertheless, it occurs without suitable planning or monitoring, a fact which might be causing several unknown environmental impacts. In Brazil, most of the reintroduction work of birds is performed with Psittacidae species, hardly been conducted with other bird groups. In CETAS, the main destination given to animals is releasing them in the wild‟. Most releases, however, take place without particular criteria or later monitoring. It is recommended here that the specimens captured by CETAS could be used as source populations in reintroduction programs, aiming at the creation of protocols of release, with more efficient methodologies. Besides that, the intensive capture of animals from the wild leads to a consequent decrease in their populations. As some of these animals are kept in CETAS, making use of them in such reintroduction programs and respecting the necessary criteria might decrease the negative effect created by the ongoing capture pressure in several ecosystems.